A novel technique combining the cyclic steam stimulation and top gas injection for increasing heat efficiency. Issue 2 (4th March 2018) - Suranto, A. M.
Abstract: In the first production period of cyclic steam stimulation (CSS), the oil production rate becomes high due to reducing oil viscosity and increasing reservoir. Even though the remaining heat is still available in the surroundings of the well, the production rate declines too sharply resulting from the reservoir pressure reduction. This paper aims to maintain the oil production rate, which utilizes the remaining heat in the reservoir with a gas top injection. After the oil production rate declines, the gas is injected into the top side of the formation which pushes crude oil to the lower part of the reservoir. Finally, the crude oil moves to the production perforation. The result indicates that the optimum volume gas injection is 6500 MMSCF. In such method, increasing reservoir thickness will be more favorable because the gas spreads more laterally and dissolves to the oil phase. In the case of extended cycle production time, the steam effectiveness will increase. To get the most favorable operation condition, the reservoir thickness must be more than 20 ft. In the optimum case, the cumulative oil production increases 3.5 times and the cumulative steam oil ratio decreases 60% compared to CSS-conventional.